390. ACUTE NUTRITIONAL AND FUNCTIONAL STATUS CHANGES IN PATIENTS UNDERGOING ESOPHAGECTOMY FOR CANCER. (24th September 2022) - Lidoriki, Irene; Syllaios, Athanasios; Mylonas, Konstantinos; Michalinos, Adamantios; Gazouli, Maria; Karavokyros, Ioannis; Liakakos, Theodoros; Schizas, Dimitrios
Abstract: Nutritional status of esophageal cancer patients who undergo esophagectomy is significantly exacerbated postoperatively. The aim of this study is to investigate changes in nutritional status and muscle function between preoperative period and the time of hospital discharge in cancer patients undergoing esophagectomy. The study sample consisted of 70 patients with esophageal (n = 13) and gastroesophageal junction cancer (n = 57) who were admitted for surgery in our Department between September 2015 and February 2020. Out of them, 52 patients underwent Ivor-Lewis esophagectomy, while 18 patients underwent McKewon esophagectomy. The preoperative evaluation of nutritional status was based on Patient Generated Subjective Global Assessment (PG-SGA), while the preoperative assessment of muscle function was based on Handgrip Strength (HG). Weight loss and anthropometric measurements were also recorded. Patients' follow-up was done at the time of hospital discharge. Patients' mean length of stay was 17.7 ± 12.5 days. Mean postoperative involuntary weight loss was 6% ± 3%. HG dominant hand was significantly lower at the time of discharge (−3.02 ± 3.80 kg, p < 0.001) compared to preoperative levels. Moreover, a significant change was observed for PG-SGA score (+2.61 ± 1.73) indicating greater rates of impaired nutritional status. There was a significant reduction in BMI (−3.7 ± 2.47 kg/m2, p < 0.001) and in arm circumference values (−0.8 ± 0.03 cm, p < 0.05), whereas no statistically significant alterations were observed in triceps skinfold measurements postoperatively (−0.007 ± 0.49, p = 0.368). Esophageal cancer patients who undergo esophagectomy exhibit overt deterioration of nutritional and functional status during the postoperative course. Timely nutritional interventions are of great significance in order to avoid patients underfeeding and improve patients' postoperative outcome.